Magnetic properties of TiCx/C nanocomposites - Guskos, N.; V. Likodimos; Glenis, S.; Zolnierkiewicz, G.; Typek, J.; Lin, C.L.; Biedunkiewicz, A. (Journal of Non-Crystalline Solids, 2008)
The magnetic properties of nanocrystalline titanium carbide dispersed in a carbon matrix (TiCx/C) prepared by the non-hydrolytic sol-gel process have been studied by dc magnetization measurements. The superconducting phase of titanium carbide has been observed at low temperatures with the onset of the superconducting transition temperature Tc at about 3.5 K, superimposed on a ferromagnetic component. At T > Tc the magnetic response of TiCx/C is determined by the interplay of the ferromagnetic contribution with the paramagnetic/diamagnetic signal of the metallic system and the contribution of exchange coupled paramagnetic ions. Moreover, significant differences are observed in the magnetic response for samples of the same preparation batch, indicative of the magnetic/electronic inhomogeneity of nanocrystalline titanium carbide which is important for its practical applications.
cited By 5